Analisis Dasar Kebijakan Menteri ATR/BPN dalam Penetapan Hak Pengelolaan Atas Tanah Ulayat - Yolva Febreight Arthania; Lego Karjoko; Sapto Hermawan (Universitas Sebelas Maret, 2026)
Important resources Management rights over customary landnare a resource for human life and community welfare. Human life and community welfare are management rights over customary land. This study looks atnthe role of the state innland management, relevant laws, and land management rights, over land and natural resources. relevant laws, and constitutional rights to landnand natural resources. The aim is to evaluate how well the current laws in place and support the interests ofnthe community. Protect andnrealize the interestsnof the community. Collected through literature studies and using a socio-legal research approach along with a conceptual and legal framework. The results of the study emphasize then need for the government to establish a complete and clear legislative framework for land management, as well as the recognition and defense of 'indigenous peoples' land rights. To address land inequality and ensure equitable and sustainable use and distribution of land resources, this study suggests agrarian reform.